Perancangan dan Pembuatan Sistem Informasi Penggajian Karyawan pada PT. Kiki Anugerah Rasa Medan - Arief Rahman Hakim (PT. ALHAFI BERKAH INDONESIA, 2025)
Salary is payment in the form of money that an employee receives, the result of his contribution as an employee and his ideas for achieving company goals. At PT. Kiki Rasa Medan Indonesia Management in the payroll sector still applies a manual / conventional payroll system with the help of Microsoft Excel. This can cause errors when calculating salaries. As a new and developing company, PT. Kiki Anugerah Rasa Medan Indonesia needs a data processing application that can help process employee payroll data quickly, precisely and accurately. The method used in this payroll system is the waterfall method, namely a structured framework that is arranged sequentially in an effort to develop an information system (software). This application was made using the CodeIgniter framework and also web programming using PHP.